Digital Learning: Differentiated Teaching Models using e-Twinning - I Communicate With My Neighbor Through Culture And Tradition: e - Twinning Project - Chaidi, Irene; Drigas, Athanasios (Technium Education and Humanities, 2022)
One of the main goals of Special Education and E-learning for people with disabilities is the development and improvement of social communication, the interaction with those around them, and the socio-emotional empowerment of students for their inclusion as active and equal members in a privileged society as people - students with disabilities present deficits in the field of social skills. The area of social skills is considered one of the important areas of the individual’s development and for its development and improvement, the basic condition is the existence of motivation. Motivations are the driving forces for social contacts and relationships centered on mutual understanding, active participation, and interaction of the individual. The above in Special Education and training is achieved through differentiated teaching models using ICTs and collaboration networks such as e-Twinning.